Busitema University Intellectual Property Policy - Busitema, University (Busitema University, 2020)
Busitema University Council; Vice Chancellor; Directorate of Graduate Studies, Research and Innovation; Legal Unit; University Secretary
Keywords: Busitema University Intellectual Property Policy; Busitema University; Intellectual Property Policy